Law Enforcement of SMEs Licensing in Empowerment of People's Economy Connected to Regional Autonomy in North Sumatra, Indonesia - Mukidi; Sinaga, Nelly Azwarni; Purba, Nelvitia; Pramono, Rudy (International Journal of Criminology and Sociology, 2021)
law enforcement on SME licensing aims to encourage the empowerment of the people's economy through improving the quality of licensing services in the regional autonomy government and for better chances in the future in North Sumatra Province. The research method used is normative legal research (juridical normative), juridical sociology, and empirical to find the truth related to the enforcement of SME licensing laws that have been stipulated in the regulations. Result of this study, the process for obtaining SME licensing in North Sumatra has been regulated through the One-Stop Integrated Licensing Service Agency based on the Minister of Home Affairs Regulation followed by Governor, Regent, and Mayor regulations through regional regulations. In the implementation, it will be carried out using technology systems and facilities or still manual. From the actual conditions, licensing services are still problematic so that to achieve the goal of law enforcement in empowering the people's economy or even to improve the economy of the community is not yet optimal, because the implementation of regulations has not been implemented properly and correctly so that the people applying for permits still have difficulty obtaining business licenses. From the results of the delegation of the authority of the regional head to the BPPTSP, it has not been fully implemented, there are still other offices that accept delegations so that permit applicants find it difficult and convoluted and their implementation overlaps in the difficult bureaucracy, finally the timeliness and expenditure of costs are not as expected.